Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: Evaluate. -|-7 + 3| A.-4 B.4 C.-10
A: -|-7 + 3|; -7 + 3 = -4
Question
Asked 6/20/2011 8:29:00 AM
Updated 4/26/2014 6:54:44 PM
1 Answer/Comment
Get an answer
New answers
Rating
3
-|-7 + 3|;


-7 + 3 = -4
Added 4/26/2014 6:54:44 PM
This answer has been confirmed as correct and helpful.
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
Solve |2x - 5| = 4.
Question
Not Answered
Updated 8/24/2014 3:46:36 PM
1 Answer/Comment
|2x - 5| = 4

2x - 5 = -4 or 2x - 5 = 4

2x - 5 = -4;
2x = -4 + 5;
2x = 1;
x = 1/2;

2x - 5 = 4;
2x = 4 + 5;
2x = 9;
x = 9/2;

x = 1/2 or x = 9/2
Added 8/24/2014 2:47:21 PM
This answer has been confirmed as correct and helpful.
Confirmed by andrewpallarca [8/24/2014 3:46:37 PM]
Solve the following system of equations by the substitution method. "5x = y + 6," "2x - 3y = 4"
Question
Not Answered
Updated 9/14/2014 1:09:10 AM
6 Answers/Comments
janezshun, please make sure to clearly type your solutions by using proper spacing.
Added 9/10/2014 7:00:16 AM
Hi andrew , for these question, Can I simplify or didn't use to add the calculation steps? I think I can't simplify it ,because the question asked to use the substitution method.
Added 9/10/2014 8:01:36 AM
The solution for 5x = y + 6, 2x - 3y = 4 is x = 14/13, y = -8/13.
From 5x = y + 6 , we can get y = 5x - 6, which we can put it into the 2th equation.
2x - 3y = 4
2x - 3 (5x - 6) =4
-13x + 18 =4
x = 14/13

put x = 14/13 into the y = 5x - 6 , we can get the value of y
y= 5x - 6
y= 5*14/13 - 78/13
y= 70/13-78/13
y= - 8/13
Added 9/14/2014 1:09:10 AM
Evaluate. -|-7 + 3|
Weegy: Two Negatives would equal a positive so the equation would be 7+ -3= Which would equal a positive 4 (More)
Question
Expert Answered
Updated 1/12/2015 8:55:41 AM
1 Answer/Comment
-|-7 + 3| = -|-4| = -4
Added 1/12/2015 8:55:37 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [1/12/2015 9:02:42 AM]
Simplify (5ab^4 c)(-abc^2).
Question
Expert Answered
Updated 6/6/2015 12:20:43 PM
1 Answer/Comment
(5ab^4 c)(-abc^2)
= -5a^2b^5c^3
Added 5/3/2015 3:08:35 AM
This answer has been confirmed as correct and helpful.
Confirmed by jeifunk [6/6/2015 12:20:39 PM]
Evaluate the following expression. (8^1)^0
Question
Not Answered
Updated 6/20/2011 12:32:45 PM
1 Answer/Comment
Anything to the power of 0 equals 1, except 0^0. The answer is 1.
Added 6/20/2011 12:32:45 PM
This answer has been confirmed as correct and helpful.
Confirmed by Andrew. [9/28/2016 7:08:17 AM]
26,995,828 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
Popular Conversations
True or false? Stress has an effect on every system of the body.
Weegy: what is the question?
6/14/2018 12:05:59 PM| 2 Answers
What's 3 * 4
Weegy: Synonyms for the word "say" which are bigger in length and in impact, are communicate, ...
6/16/2018 8:51:59 PM| 2 Answers
S
L
Points 230 [Total 248] Ratings 0 Comments 160 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 105 [Total 256] Ratings 1 Comments 5 Invitations 9 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 1 Comments 0 Invitations 1 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.